Strong XUV irradiation of the Earth-sized exoplanets orbiting the ultracool dwarf TRAPPIST-1 - Wheatley, Peter J.; Louden, Tom; Bourrier, Vincent; Ehrenreich, David; Gillon, Michaël (Monthly notices of the Royal Astronomical Society. Letters, 2017)
We present an XMM–Newton X-ray observation of TRAPPIST-1, which is an ultracool dwarf star recently discovered to host three transiting and temperate Earth-sized planets. We find the star is a relatively strong and variable coronal X-ray source with an X-ray luminosity similar to that of the quiet Sun, despite its much lower bolometric luminosity. We find LX/Lbol = 2–4 × 10−4, with the total XUV emission in the range LXUV/Lbol = 6–9 × 10−4, and XUV irradiation of the planets that is many times stronger than experienced by the present-day Earth. Using a simple energy-limited model, we show that the relatively close-in Earth-sized planets, which span the classical habitable zone of the star, are subjected to sufficient X-ray and EUV irradiation to significantly alter their primary and any secondary atmospheres. Understanding whether this high-energy irradiation makes the planets more or less habitable is a complex question, but our measured fluxes will be an important input to the necessary models of atmospheric evolution.